ANALISIS INTENSITAS PENGGUNAAN APLIKASI MEDIA SOSIAL DAN DURASI AKTIVITAS DI MEDIA SOSIAL TERHADAP KINERJA AKADEMIK MAHASISWA UNIVERSITAS PEMBANGUNAN PANCA BUDI MEDAN - Muhammad Evan jinanda; Hakim Gilangkara, Bagus Dwi Nugraha, Fauzi Bima Ramadhan, Muhammad Fajrotu Syahri Dalimunthe, Supiya (Jurnal Komunikasi, 2025)
This study examines the influence of social media application usage intensity and duration of social media activities on the academic performance of students at Universitas Pembangunan Panca Budi Medan. Using a quantitative approach with a correlational design, this study involved 99 randomly selected students as samples. Data was collected through online questionnaires and analyzed using multiple linear regression. The results show that the intensity of social media use has a significant negative effect on academic performance, with a t-count value of -8.062, which is greater than the t-table (1.66) and a significance of 0.000. Conversely, the duration of social media activities has a significant positive effect on academic performance, with a t-count value of 7.342, which is greater than the t-table (1.66) and a significance of 0.000. Simultaneously, both variables also show a significant influence on students' academic performance, with an F-count value of 54.505, which is far greater than the F-table value (3.09) and a significance of 0.000. These findings indicate the importance of a balanced approach to social media use, with educational institutions needing to encourage constructive and academically-oriented social media use